2023
DOI: 10.1186/s12938-023-01074-2
|View full text |Cite
|
Sign up to set email alerts
|

Continuous relative phases of walking with an articulated passive ankle–foot prosthesis in individuals with a unilateral transfemoral and transtibial amputation: an explorative case–control study

Abstract: Background A mechanical ankle–foot prosthesis (Talaris Demonstrator) was developed to improve prosthetic gait in people with a lower-limb amputation. This study aims to evaluate the Talaris Demonstrator (TD) during level walking by mapping coordination patterns based on the sagittal continuous relative phase (CRP). Methods Individuals with a unilateral transtibial amputation, transfemoral amputation and able-bodied individuals completed 6 minutes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The data of the inertial measurement units will be used to evaluate coordination patterns between hip, knee and ankle joints or segments based on continuous relative phase plots. Biomechanical data will be analysed and purified in Matlab (The MathWorks Inc., Massachusetts, United States) following the methods described in Lathouwers et al (2023) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The data of the inertial measurement units will be used to evaluate coordination patterns between hip, knee and ankle joints or segments based on continuous relative phase plots. Biomechanical data will be analysed and purified in Matlab (The MathWorks Inc., Massachusetts, United States) following the methods described in Lathouwers et al (2023) [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Complementing these findings, Cheng et al 14 demonstrated that a 12-week prosthetic gait training program can significantly enhance walking speed and limb coordination. Esposito et al 18 focused on pelvis-trunk coordination across different walking speeds, while Lathouwers et al 16 assessed gait patterns using an articulated passive ankle–foot prosthesis, highlighting areas for further research in joint coupling variability during gait in individuals with transfemoral and transtibial amputations. Collectively, these studies underscore the importance of nonlinear dynamic analysis in advancing our understanding of prosthetic gait dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Since different prosthetic devices may produce external perturbations to their system (ie, gait pattern), it is critical to determine the device that minimises these perturbations and allows the individual to reach his or her most stable walking pattern. While previous literature describes the application of relative phase (RP) analysis to individuals with lower limb loss,14–17 most of the studies focus on coordination between the pelvis and trunk,14 15 17 and one describes the intralimb (ie, within limb) coordination of the lower extremities 16. To date, only one study has investigated continuous gait interlimb (ie, between limbs) coordination and stability in individuals with lower limb loss 18.…”
Section: Introductionmentioning
confidence: 99%